2009
DOI: 10.1007/s00253-009-2289-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of corrosive bacterial consortia isolated from petroleum-product-transporting pipelines

Abstract: Microbiologically influenced corrosion is a problem commonly encountered in facilities in the oil and gas industries. The present study describes bacterial enumeration and identification in diesel and naphtha pipelines located in the northwest and southwest region in India, using traditional cultivation technique and 16S rDNA gene sequencing. Phylogenetic analysis of 16S rRNA sequences of the isolates was carried out, and the samples obtained from the diesel and naphtha-transporting pipelines showed the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(105 citation statements)
references
References 32 publications
4
95
0
6
Order By: Relevance
“…It has been reported that it can also accumulate heavy metal (Fang et al, 2010;Kanaly et al, 2000;Turgay et al, 2012;Rajasekar et al, 2010), grow on explosives such as pentaerythritol tetranitrate (PETN) and 2,4,6-trinitrotoluene (TNT) as sole nitrogen source (Binks et al, 1996;French et al, 1998) and it can decontaminate water from herbicides (Chena et al, 2009;Sakultantimetha et al, 2001;Ngigi et al, 2012). Also, this microorganism has been isolated from materials contaminated with crude oil.…”
Section: Molecular Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that it can also accumulate heavy metal (Fang et al, 2010;Kanaly et al, 2000;Turgay et al, 2012;Rajasekar et al, 2010), grow on explosives such as pentaerythritol tetranitrate (PETN) and 2,4,6-trinitrotoluene (TNT) as sole nitrogen source (Binks et al, 1996;French et al, 1998) and it can decontaminate water from herbicides (Chena et al, 2009;Sakultantimetha et al, 2001;Ngigi et al, 2012). Also, this microorganism has been isolated from materials contaminated with crude oil.…”
Section: Molecular Identificationmentioning
confidence: 99%
“…However, other researchers have reported the isolation and ability of this microorganism to grow and degrade crude oils, which are rich in alkanes . Rajasekar et al (2010) reported the isolation of K. oxytoca in diesel and naphtha pipelines in the Northwest and Southwest regions in India. They have also isolated other 10 bacteria (Serratia marcescens ACE2, Bacillus subtilis AR12, Bacillus cereus ACE4, Pseudomonas aeruginosa AI1, Pseudomonas stutzeri AP2, Bacillus litoralis AN1, Bacillus sp., Bacillus pumilus AR2, Bacillus carboniphilus AR3 and Bacillus megaterium AR4).…”
Section: Molecular Identificationmentioning
confidence: 99%
“…Migration was assessed qualitatively by examining the circular zone from the point of inoculation (streaking point) formed on the plates. Surface hydrophobicity of the EN2 was assessed by microbial adhesion to solvents (MATS) method following the protocol of Bellone-Fontaine et al [29]. This method is based on the comparison of microbial cell affinity to polar and non-polar solvents (chloroform, hexadecane, ethyl acetate and decane).…”
Section: Biofilm Motility Assay and Surface Characteristics Of Bacteriamentioning
confidence: 99%
“…Collected corrosion products were crushed into a fine powder and used for FTIR analysis. For bacterial curve, the biofilm formed on coupons from each system was scraped and the total viable count was measured by standard plate count method [29].…”
Section: Biocorrosion Studymentioning
confidence: 99%
“…One consequence of the ability of microorganism to oxidize metals is biocorrosion. Biocorrosion of metals and their alloys can occur whether they are submerged in water, buried in soil or exposed to the atmosphere; this is because the microorganisms that cause biodeterioration are widely distributed (Rajasekar et al, 2010). as pipelines, cooling circuits, production lines, injections lines and storage tanks.…”
Section: Introductionmentioning
confidence: 99%